Kajian Kebugaran Jasmani Siswa Putra Kelas XII SMA Negeri 1 Simo Kabupaten Boyolali Tahun 2024 - Wijaya, Tony; Dwijayanti, Karlina; Sunjoyo (MAN Insan Cendekia Jambi, 2024)
Physical education serves an important role in forming people who are not only physically fit, but can also overcome life's challenges with a tough mind and good nature. However, physical fitness is also an important aspect in participating in physical education lessons and in daily activities, and is often a concern in efforts to improve achievement and learning outcomes. This study aims to understand the level of physical fitness among high school students. The survey was conducted on 113 students at SMA N 1 Simo using descriptive and quantitative research methods by collecting data through the TKPN testing tool. The test carried out by students serves to assess the extent of physical fitness of class XII male students at SMA N 1 Simo. The results of student data collection show that the physical fitness condition of class XII male students at SMA N 1 Simo is categorized as poor with a percentage of 51% for 58 male students. These findings may provide deeper insight into methods for measuring students' physical fitness in high schools.